1985
DOI: 10.1002/j.1460-2075.1985.tb03693.x
|View full text |Cite
|
Sign up to set email alerts
|

The human ubiquitin multigene family: some genes contain multiple directly repeated ubiquitin coding sequences.

Abstract: Ubiquitin coding sequences were isolated from a human genomic library and two cDNA libraries. One human ubiquitin gene consists of 2055 nucleotides and codes for a polyprotein consisting of 685 amino acid residues. The polyprotein contains nine direct repeats of the ubiquitin amino acid sequence and the last ubiquitin sequence is extended with an additional valyl residue at the C‐terminal end. No spacer sequences separate the ubiquitin repeats and the coding regions are not interrupted by intervening sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
192
0
2

Year Published

1988
1988
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(210 citation statements)
references
References 33 publications
12
192
0
2
Order By: Relevance
“…56 If one considers only one repeat, L. infantum polyubiquitin has only two and four amino acid differences (at positions 14, 52, 70, and 77) relative to canine and human ubiquitin, respectively. Nevertheless, it has been shown that patients with chronic Chagas' disease produce antibodies against T. cruzi ubiquitin, 57 the monomer of which has only three amino acid differences relative to human ubiquitin.…”
Section: Discussionmentioning
confidence: 99%
“…56 If one considers only one repeat, L. infantum polyubiquitin has only two and four amino acid differences (at positions 14, 52, 70, and 77) relative to canine and human ubiquitin, respectively. Nevertheless, it has been shown that patients with chronic Chagas' disease produce antibodies against T. cruzi ubiquitin, 57 the monomer of which has only three amino acid differences relative to human ubiquitin.…”
Section: Discussionmentioning
confidence: 99%
“…The primers were designed on the basis of the sequence data for human polyubiquitin C (Wiborg et al, 1985). A polymerase chain reaction (PCR) was performed using PuRe Taq Ready-To-Go PCR Beads (Amersham, Biosciences, Piscataway, USA) with different primers sets ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…encode for polyubiquitin that contains three, four, or nine repeats of ubiquitin, while others encode for only one ubiquitin sequence (Wiborg et al, 1985). In present study, two incomplete units of ubiquitin were amplified from the camel genomic DNA using specific primers.…”
Section: Setmentioning
confidence: 99%
“…10 mg of total RNA was fractionated on 1% agaroseformamide gel and transferred to nylon membrane (HybondN, Amersham) according to [10]. Probes for calmodulin, chondroitin sulfate proteoglycan core protein, clusterin, ubiquitin and GAPDH were obtained, respectively, by labeling of the insert of plasmid p21, p8.5 [11], pSP64-60HE [12], pHUB14.38 [13] and pGAPD-13 [14], respectively, with [32p]dCTP by random primers using the megaprime-labeling systems (Amersham). Probes for RP8, glutathione S-transferase (made from plasmids pRP-8 [15], pGST2 [16]) were labeled with [32p]dCTP by PCR of pBluescript inserts.…”
Section: Rna Analysismentioning
confidence: 99%